2022
DOI: 10.1177/09544062221090082
|View full text |Cite
|
Sign up to set email alerts
|

Application of machine learning approaches to predict joint strength of friction stir welded aluminium alloy 7475 and PPS polymer hybrid joint

Abstract: Vehicle weight has been a critical concern in the aerospace and automobile industries for decades. Integrating dissimilar aluminium and polymer hybrid structures is beneficial for weight reduction without affecting structural performance. In the present work, aluminium alloy 7475 and polyphenylene sulfide (PPS) sheets were joined using the friction stir welding (FSW) technology in lap joint configuration. A series of FSW experiments have been performed by the design matrix developed using response surface meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Scanning electron microscope (SEM) and EDX analyses were conducted using a Zeiss Merlin VP compact SEM with a Bruker XFlash EDX detector. The accelerating voltage was 15 kV, and the working distances were approximately between [12,22] mm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scanning electron microscope (SEM) and EDX analyses were conducted using a Zeiss Merlin VP compact SEM with a Bruker XFlash EDX detector. The accelerating voltage was 15 kV, and the working distances were approximately between [12,22] mm.…”
Section: Methodsmentioning
confidence: 99%
“…This paper delves into the intricate interplay between selfsensing capabilities and the piezoelectric properties of PZT and BT, with a particular focus on their potential application in aluminium components. Aluminium, widely used for its lightweight and corrosion-resistant properties in aerospace, automotive, and structural applications, holds significant promise for implementing advanced SHM technologies [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Prasad et al 20 implemented the FSW of PP/Al 2 O 3 nanocomposites and stated that the increase of rotational speed improved the tensile and flexural strengths of weld joint, while the addition of Al 2 O 3 content up to 10 wt% increased the hardness and tensile strength of the weld joint. The feasibility of FSW process of the polymer nanocomposites was also investigated by Azarsa et al, 21 Alyali et al 22 and Junior et al 23,24 The FSW of dissimilar materials such as aluminium alloy 7475 and polyphenylene sulfide thermoplastic polymer was performed by Sandeep et al 25,26 They reported that the maximum tensile strength attained at tilt angle of 2°, welding speed of 5.12 mm/min and tool rotational speed of 1185.92 rpm. In accordance with the metallographic investigation, they also observed that different pin profiles of welding tool have distinct bonding mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Investigated was how well machine learning methods might predict the joint's TLS. The most effective method for predicting the TLS was found to be the support vector machine (SVM) framework with RBF kernel [23]. Guan et al [24] provided a method for creating machine learning models driven by force data that accurately anticipate faults and their categories in friction stir welding (FSW).…”
Section: Introductionmentioning
confidence: 99%